Boomerang Technique, The Buccal Mucosal Grafting Harvesting Model for Long Urethral Stricture Urethroplasty; A Case Series - Hosseini, Jalil; Fallahkarkan, Morteza; Salimi, Hojjat; Ghiasy, Saleh (Urology Journal, 2020)
Purpose: Currently, three methods are implicated in cases of long urethral stricture including harvesting buccal mucosa of inner cheeks, harvesting lip mucosa and finally lingual mucosal graft. This study evaluated the feasibility, safety and morbidity of our “Boomerang shape” technique used for graft retrieval from the inner cheeks to repair long urethral defect cases which are usually 12-15 cm in length and 2.5 cm in width. Materials and Methods: The Kilner-Doughty mouth retractor is inserted to give access to the donor site. Initially, the internal surface of the right/left cheek is cleaned with a solution containing 10% povidone-iodine. Then, Stensen’s duct, located at the level of the second molar is identified and the desired size of the graft is measured and marked in a boomerang shape, 1.5 cm from the Stensen’s duct and 1.5 cm from the edge of the cheek. To decrease submucosal bleeding from the harvest site, 1% lidocaine combined with a 1:100,000 epinephrine solution is injected using a 25-gauge long needle. The outlines of the graft are drawn by using a scalpel through the mucosa. Then, the outlined graft is sharply dissected and removed, leaving the muscle intact. A 5-0 polyglactin continuous suture is used for the closure of the harvest site. The standard graft harvested from the cheek should be 12-15 cm in length and 2.5 cm in width. Results: Between 2017-2019, five adults have had their mucosal grafts harvested by the “Boomerang shape” technique in our center. No donor site complications were observed. Moreover, no urethral strictures or diverticulum occurred and the functional outcomes were satisfactory in all patients. Conclusion: Our routine technique of harvesting the buccal mucosa from the cheek is secure and easily performable by any surgeon. It has minimal incidence of intra and post-operative complications.